President's Podium: SYVW RIP or OMT?*: Retire It Permanently or One More Time? - Adamack, T.L. (Canadian Journal of Optometry, 1989)
Save Your Vision Week in Canada 1989 (SYVW) is upon us once again and it seems as appropriate a time as any to raise a few reasonable questions about the event.